Needs Analysis of Multicultural-Based Character Education in The Nusantara Dance I Course at The Department of Performing Arts Education - Nurlia Djafar; Maryam Rahim; Suleman Bouti; Mohamad Zubaidi (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze students’ learning needs and perceptions in the Tari Nusantara 1 course at Universitas Negeri Gorontalo, focusing on the integration of multicultural and character-based education through traditional dance. Using a mixed-methods approach combining quantitative surveys and qualitative interpretation, data were collected from 16 respondents through questionnaires. The findings reveal that all students (100%) demonstrate a strong motivation to understand Indonesia’s cultural richness, develop traditional dance skills, and strengthen their moral and cultural identity. Students perceive dance not merely as artistic performance but as a medium for building self-confidence, discipline, and pride in national heritage. Overall, the study concludes that Tari Nusantara 1 should be designed as a holistic, multicultural learning space that balances cognitive, affective, and psychomotor development. Such an approach fosters character formation, cultural awareness, and professionalism, preparing students as future cultural preservers in the global era.